COMMON PERCEPTION OF CHINESE COOPERATION IN AFGHANISTAN - Valacchi, Francesco (European Scientific Journal, ESJ, 2015)
In the article I will try to define Chinese macro-strategy in investing in Afghanistan. Then, analyzing data collected on the field with an interview, I will try to examine Afghan perception of Chinese presence. After data analysis I will try to establish if Chinese strategy is useful to the picture that China wants to show of its presence in Afghanistan and what are the possible correction for making it much efficient.